Islamic transformations in the periphery of Maluku, Indonesia. Issue 138 (4th May 2019) - Kaartinen, Timo
ABSTRACT: The article explores Islam as an element of the social and symbolic formations created in the context of long-distance trade relations in the Aru and the Kei islands of southeast Maluku. The Muslim migrants and traders who settled in the area in the early colonial period created places that served as entry points to the local, autochthonous society. Even as these sites allowed Muslims to control access to local cultural domains, they allured local people with possible access to trade wealth and mobility. By creating conceptual and tangible boundaries around the indigenous domain, early Islam anticipated the contrast between universally valid religious convictions and materially embedded cultural forms. This contrast became significant after the large-scale conversions to Christianity and Islam in the late colonial period. Islam was also transformed by its interaction with various cosmopolitan discourses, but it has remained more accommodating than Christianity towards socially embedded ritual practices and material symbols. This raises the question whether 'cultural Islam' should be defined by its neutral, apolitical attitude towards the secular state which is complicated by the fact that the culturally embedded Islam in Maluku took form in the absence of centralised state power.